Reflection of the 1930´s British Society in Graham Greene´s Brighton Rock - Nešetřilová, Iva (Univerzita Pardubice, 2017)
This paper examines and analyses the reflection of British Society in the novel Brighton Rock by Graham Green. The first part explores the situation in Britain around the 1930s, the period when the book was written and published, and briefly focuses on the changing landscape brought about by the Depression and aftermath of the First World War. The emphasis is confined mostly to how these changes affected the lower classes, and a brief description of what constitutes working class is provided. This is followed by the main part of the thesis, which is centred on the book Brighton Rock and how it represents the lower classes, specifically in relation to changing values and deflection from religious beliefs. Further subchapters explore some of the effects of these changes, with emphasis on crime and morality, and the concept of heaven and hell. Brighton is also explored as a setting for the book in relation to its urban atmosphere and typography. In addition, a literary analysis on some of the main characters demonstrates how life choices affect the ability to advance or be led to damnation.
Odraz Britské společnosti 30. let v románu Brighton Rock od Gragma Greena
Keywords: crime; morality; religion; societies; classes; zločinnost; morálka; náboženství; společnosti; třídy